Peran Dinas Kearsipan dan Perpustakaan Kabupaten Gayo Lues Dalam Mengembangkan Perpustakaan Berbasis Inklusi Sosial - Siti Aminah (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2023)
This research  titled is  "The Role of the Gayo Lues District Archive and Library Agency in Developing a Socially Inclusive Library." The research problem is as follows: 1) the implementation of the development of a socially inclusive library, 2) the opportunities and challenges in developing a socially inclusive library, and 3) the efforts made by the Gayo Lues District Archive and Library Agency in facing these challenges. The purpose of this research is to determine the implementation of the development of a socially inclusive library, the opportunities and challenges faced, and the efforts made by the Gayo Lues District Archive and Library Agency. This research uses a qualitative method with a descriptive approach. The data collection techniques used are observation, interview, and documentation. The results of the research show that the implementation of the development of a socially inclusive library in the Gayo Lues District Archive and Library Agency is going well, with librarians actively involved in revitalization training, library management training, and advocacy through Peer Learning Meetings. The opportunities in this inclusive social library include business opportunities, other social opportunities, and reducing poverty. The Gayo Lues District Archive and Library Agency faces challenges in developing a socially inclusive library, such as lack of cooperation, limited space, and limited budget. Efforts to overcome these challenges include cooperation with other parties and optimal utilization of the budget provided by the center. Keywords: Library Development, Social Inclusion, Gayo Lues District Archive and Library Agency.